An Influence of a Sort of Feeding on a Formation of Children’s Health at Early age - S. N. Polukeeva; V. D. Pavlenko; T. V. Strelnikova; I. I. Kalashnikova; M. I. Iljina (Медицинский вестник Юга России, 2011)
Purpose: Studying of a sort of feeding influence on a state of children’s health at the early age.Materials and Methods. 113 children of early age from 1 year and 1 month till 3 years old were under observation. They were divided into 2 groups. The first group was made up of 92 children who were on exclusively breast feeding till 4-6 months and the comparison group included 21 children on early artificial feeding. The integrated assessment of a health state was performed and it was studied the chldren’s morbidity of both groups.Results: A comparison of critical parameters of physical and neuropsychоlogical development of the both investigated groups of children in dynamics didn’t not reveal any authentic distinctions. The general morbidity of these children were on exclusively breast feeding till 4-6 months was authentically lower, that.Summary: Receiving resalts specifies an essential role of exclusively breast feeding in formation children’s health at early age.